2017
DOI: 10.1136/bmjopen-2017-018861
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the Mayo Clinic Cohort Study of Oophorectomy and Aging-2 (MOA-2) in Olmsted County, Minnesota (USA)

Abstract: PurposeThis cohort study was established to investigate the effects of unilateral and bilateral oophorectomy on the ageing processes in women.ParticipantsWe used the records-linkage system of the Rochester Epidemiology Project (REP, http://www.rochesterproject.org) to identify 570 women who underwent unilateral oophorectomy and 1653 women who underwent bilateral oophorectomy in Olmsted County, Minnesota from 1988 through 2007 (20 years). Each woman was matched by age (±1 year) to a population-based referent wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 37 publications
1
49
2
Order By: Relevance
“…Uterine prolapse is uncommon at a young age; however, in our study, uterine prolapse was the clinical indication in 29 (18.47%) women and was reported in 38 (24.20%) women, all of whom were older than 25 years. This frequency of prolapse is comparable to a study from Pakistan, which reported prolapse in 24% of hysterectomies, as compared to 37.5% in patients from India and 20% from the United States [23,25,27].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Uterine prolapse is uncommon at a young age; however, in our study, uterine prolapse was the clinical indication in 29 (18.47%) women and was reported in 38 (24.20%) women, all of whom were older than 25 years. This frequency of prolapse is comparable to a study from Pakistan, which reported prolapse in 24% of hysterectomies, as compared to 37.5% in patients from India and 20% from the United States [23,25,27].…”
Section: Discussionsupporting
confidence: 84%
“…An international cohort study on women undergoing simultaneous hysterectomy and oophorectomy for uterine pathologies has reported that ovarian cancer was reported in only 1.5% of bilateral and 1.9% of unilateral oophorectomies removed with the hysterectomy specimen and that benign conditions or normal histology was present in the majority of these oophorectomies [26]. Literature has verified that ovarian conservation for women undergoing hysterectomy for benign causes has long-term survival benefits; for many years post-menopause, the ovaries continue to synthesize testosterone and androstenedione, which is converted to estrogen [27]. Removal of hormonally active ovaries is associated with increased risk of coronary artery disease, hypertension, osteoporosis, fractures, and psychological problems such as depression, Parkinson's disease, schizophrenia, and dementia, as demonstrated in large-cohort studies [28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The Mayo Clinic Cohort Study of Oophorectomy and Aging-2 (MOA-2) is a population-based cohort study that includes women who underwent BSO before age 50 years and before reaching natural menopause from 1988 through 2007 and an age-matched control group who had not undergone bilateral oophorectomy before age 50 years. 5 The Mayo Clinic Study of Aging (MCSA) is another population-based cohort study, which includes participants with normal cognitive aging, mild cognitive impairment, and dementia. 6 All MCSA participants are invited to undergo MRI and Pittsburgh compound B (PiB) positron emission tomography (PET).…”
Section: Methodsmentioning
confidence: 99%
“…Women were identified as part of the Mayo Clinic Cohort Study of Oophorectomy and Aging-2 (MOA-2) as described extensively elsewhere (15)(16)(17). All of the data used for this study were derived from the medical records linkage system of the Rochester Epidemiology Project, which has been described elsewhere (18)(19)(20)(21).…”
Section: Cohort Definition and Comorbidities At Index Datementioning
confidence: 99%
“…Medical comorbidities present at the index date were electronically abstracted using selected International Classification of Diseases (ICD) diagnosis codes (ICD-8 or ICD-9) (22). Women needed to have at least two diagnostic codes in a given category separated by .30 days to avoid false positive diagnoses (17). Medical records were manually reviewed, and oophorectomy status was confirmed by trained study personnel (primarily L.G.R.).…”
Section: Cohort Definition and Comorbidities At Index Datementioning
confidence: 99%